2010
DOI: 10.1021/ic902135t
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Investigations of the Homoleptic Tris(dithiolene) Complexes [M(dddt)3]q(q= 3, 2 ; M = Nd3+and U3+/4+) Related to Lanthanide(III)/Actinide(III) Differentiation

Abstract: The structures of the homoleptic lanthanide and actinide tris(dithiolene) complexes [M(dddt)(3)](q-) (q = 3, M = Nd(3+) and q = 3 or 2, M = U(3+/4+)) have been investigated using relativistic Density Functional Theory (DFT) computations including spin-orbit corrections coupled with the COnductor-like Screening Model (COSMO) for a realistic solvation approach. The dithiolene ligands are known to be very efficient at stabilizing metal high oxidation states. The aim of the work is to explain the peculiar symmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Our previous work [105][106][107][108][109] and several recent studies [68,69,[116][117][118][119][120] have shown that ZORA/BP86/TZP computations reproduce experimental geometries and ground state properties of f-element compounds with a satisfying accuracy.…”
Section: Description Of the Model And Computational Detailsmentioning
confidence: 80%
See 1 more Smart Citation
“…Our previous work [105][106][107][108][109] and several recent studies [68,69,[116][117][118][119][120] have shown that ZORA/BP86/TZP computations reproduce experimental geometries and ground state properties of f-element compounds with a satisfying accuracy.…”
Section: Description Of the Model And Computational Detailsmentioning
confidence: 80%
“…Spin-orbit corrections to the energy difference between the high spin (HS) and BS states have not been considered. These corrections are of atomic nature [105][106][107][108][109][110][111][112], that is, not very sensitive to the environment of the metal ion for a given oxidation state. In the present study, the metal electron configuration is 5f 2 for each U(IV) ion, whatever the HS or BS state, so that neglecting spinorbit corrections seems to be a valid assumption.…”
Section: Description Of the Model And Computational Detailsmentioning
confidence: 99%
“…60 The rapid and reversible electron transfer between the U III and U IV while the ionic radius of uranium(III) is ∼0.02 Å larger than that of cerium(III). Such deviations of U-X distances (X = C, N, I, P, S) from a purely ionic bonding model, which have been observed in a variety of analogous uranium(III) and lanthanide (III) complexes, 61,62 are explained by a stronger, more covalent actinide-ligand interaction. In these anionic and monomeric complexes, the shortening of the U-C(CN) bond length with respect to the corresponding Ce-C(CN) could be an indication of a stronger σ-donation of the ligand towards uranium rather than π back-bonding, as supported by the ν(CN) frequencies.…”
Section: Linear Metallocenes Bent Actinocenes and Half Sandwichesmentioning
confidence: 87%
“…These works revealed that the 5f orbitals in actinide complexes play a significant role in bonding, while the participation of 4f orbitals of lanthanides in bonding appears to be minimal or even negligible [135]. For instance, it was shown that the frontier MOs with important 4f metallic character in Nd III tris(dithiolene) complexes possess zero contribution from the ligands, while in the U(III) system these orbitals are delocalized over the metal and the ligands and contain a substantial 5f contribution [136]. As a result, large-core RECPs, which often provide good results for Ln III complexes, are of more limited application in the case of their actinide counterparts [137].…”
Section: The Nature Of Chemical Bonding In Ln III Complexesmentioning
confidence: 99%